DETERMINATION OF WATER QUALITY INDEX (WQI) CENTRAL JAVA PROVINCE WATER BODY BASED ON TOTAL COLIFORM - Iva Yenis Septiariva; Hashfi Hawali Abdul Matin; Novi Kartika Sari; Ariyanti Sarwono; I Wayan Koko Suryawan (Journal of Green Science and Technology, 2021)
In recent years, the Central Java Province municipal river's water quality in the area is classified as heavily polluted. Therefore, research on water quality and its pollution level needs to be carried out in the Surakarta municipal river, especially in the Central Java Province. This study aimed to determine water quality and the pollution conditions in the Surakarta municipal river and analyze the conditions of the pollution load in the river at a predetermined observation point. This research was conducted using a survey method field with secondary data. The analysis was carried out using the method water quality index (WQI). The results showed The WQI change from heavily polluted to lightly polluted was measured at several observation locations from 2016 to 2018. The changes in the measured pollution index from 2016 to 2018 by coliform.